Agricultural Workers Standard of Living During Central Chile S Agrarian Expansion, 1870-1930 - Robles-Ortiz, C; Gonzalez-Correa, I (Cambridge University Press, 2023)
The purpose of this paper is to determine trends in the wages and living standards of male agricultural labourers in Central Chile during the agrarian expansion, c. 1870-1930. We found that nominal wages increased eightfold; this is relevant because wage labour became the main rural labour regime in this period. Nominal wages rose steadily from the early 1870s until 1910, and with significant fluctuations thereafter, before plummeting with the Great Depression. Real wages also increased, but only slightly. Furthermore, during certain short periods, agricultural labourers real wages were similar to or higher than those of low-skilled urban workers. However, the persistent gap between agricultural and non-agricultural wages was one of the causal factors of the outmigration of rural workers. Copyright © The Author(s), 2021. Published by Cambridge University Press on behalf of Instituto Figuerola, Universidad Carlos III de Madrid.